Pendampingan Teaching Factory Melalui Pelatihan Komunikasi Efektif dan Literasi Keuangan Dalam Mendukung Ketahanan Pangan Berkelanjutan - Risma Nurmilah; Yuyun Sri Wahyuni; Venita Sofiani; Evi Martaseli; Ismet Ismatullah; Rinaldi Rinaldi; Reni Anggraeni (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2026)
This community service activity aims to increase the capacity of MSME actors through Teaching Factory assistance with a focus on effective communication training and financial literacy in supporting sustainable food security. The partner in this activity is the Sukabumi Entrepreneur Association (SEA) located in Sukabumi City. Problems faced by partners include low business communication skills, limited understanding of financial literacy, and lack of optimal management of MSME business administration and reporting. The method of implementing activities consists of three stages, namely observation and socialization, discussion forums (Focus Group Discussion), and the implementation of mentoring. The observation stage is carried out through direct interviews with SEA administrators and members to identify the needs and problems of partners. Furthermore, discussion forums were held to formulate solutions and develop mentoring programs that suit the needs of MSMEs. The implementation stage is carried out through offline training and mentoring involving lecturers in the fields of communication, economics, accounting, and taxation. The material provided includes effective communication, business financial management, simple financial report recording, and understanding of MSME tax administration and reporting. The results of the activity showed that participants had an increased understanding of business communication and financial literacy that could be applied in their business development. Through this activity, it is hoped that MSMEs will be able to increase business professionalism, strengthen competitiveness, and support sustainable food security in Sukabumi City.